The treasure trove of yeast genera and species described by Johannes van der Walt (1925-2011) - Maudy Th. Smith; Marizeth Groenewald (IMA Fungus)
Yeast taxonomy and systematics have in recent years been dealt with intensively primarily by a small group of individual researchers with particular expertise. Amongst these was Johannes P. van der Walt, who had a major role in shaping our current understanding of yeast biodiversity and taxonomy. Van der Walt based his taxonomic studies not only on available cultures, but also by going into the field to isolate yeasts from various substrates. This pioneering work led to the discovery of many new genera and species, which were deposited in the Centraalbureau voor Schimmelcultures (CBS) collections for future studies in taxonomy, genomics, and industrial uses. These treasures collected during more than 60 years provide an outstanding legacy to the yeast community and will continue to exist in his absence. This contribution provides a comprehensive overview of the current nomenclatural and taxonomic status of the yeast genera and species introduced by van der Walt during his career.